ANALISIS BANGKITAN PERJALANAN TERHADAP PUSAT GROSIR SURABAYA DI KAWASAN SURABAYA PUSAT - Maulana Riezal Pratama; Nugroho Utomo; Fithri Estikhamah (LPPM Universitas Abdurrab, 2024)
The pandemic has disrupted trading activities, causing business actors at the Surabaya Wholesale Center to go out of business and some business actors are still surviving today. So that their business can revive, the management of the Surabaya Wholesale Center is trying to revive consumer attraction so that the Surabaya Wholesale Center will once again be busy with visitors. Therefore, this research needs to be carried out to find out the factors that influence the number of trip generation, look for the best generation model and find out how much movement generation there is at the Surabaya Wholesale Center currently and predict the number of visitors in the projected life of the next five years. This research was conducted to analyze the impact of movement generation at this location, and predict the number of visitors at the Surabaya Wholesale Center using the multiple linear regression analysis method, which was then continued with trip generation analysis using the Detroit method. From the research results, it was found that the distribution of trips using the Detroit method was 102 trips in the next 5 years with a total growth of 13.98% per year. From the multiple linear regression equation, we get a generation equation model with the independent variable (X1) being age and the variable (X2) being the type of work, because it influences the generation (Y). The predicted number of visitors to the Surabaya Wholesale Center in the Central Surabaya area is 355,814 visitors with a growth rate visitors 20.2% in the next 5 years.